2022
DOI: 10.1038/s41416-021-01670-w
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of radiotherapy induced toxicity in head and neck cancer patients identifies a susceptibility locus associated with mucositis

Abstract: Purpose A two-stage genome-wide association study was carried out in head and neck cancer (HNC) patients aiming to identify genetic variants associated with either specific radiotherapy-induced (RT) toxicity endpoints or a general proneness to develop toxicity after RT. Materials and methods The analysis included 1780 HNC patients treated with primary RT for laryngeal or oro/hypopharyngeal cancers. In a non-hypothesis-driven explorative discovery study, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Similar associations of specific germline variants and toxicity outcomes have been described in prostate and nonsmall cell lung cancer (NSCLC) [22]. In a recent study an association with mucositis RT induced toxicity in HNSCC and a specific locus on chromosome 5 was reported [23]. Here, we proceed to analyze the association of germline variants with HNSCC rtAEs.…”
Section: Introductionmentioning
confidence: 58%
“…Similar associations of specific germline variants and toxicity outcomes have been described in prostate and nonsmall cell lung cancer (NSCLC) [22]. In a recent study an association with mucositis RT induced toxicity in HNSCC and a specific locus on chromosome 5 was reported [23]. Here, we proceed to analyze the association of germline variants with HNSCC rtAEs.…”
Section: Introductionmentioning
confidence: 58%
“…To date, genome-wide association analysis studies of radiotherapy in head and neck cancers, including nasopharyngeal carcinoma, have focused more on radiotherapy toxicity, and they have revealed a number of genetic variants associated with multiple toxicities, including acute xerostomia [ 17 ], radiotherapy-induced mucositis [ 18 ], and radiotherapy-induced brain injury. [ 19 ] Previously, we also performed a GWAS study of multiple acute radiotherapy toxicities in 1084 patients with nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Other variants in DNA damage and repair genes; XRCC2, XPD, ERCC1, ZNF24, NBN, Ku70, ATM, CHEK1, RAD51C, ERCC2, PMS1, MLH1 were associated with RT-acute toxicities, these results matched our study of the potential mechanisms of inflammatory pain induced by RT 22 . Additionally, 11 studies identified variants in genes involved in inflammatory pathways and immune systems including; TNF-α 60, 96, 99 , STING1 100 , HLA-DQB1 58 , TNFRSF1A 64 , GHRL 65 , PLA2G2F/ IIF 101 , IFNG 80 , IL12RB2 91 and NF-κβ 96 , these variants were associated with RT-induced inflammatory pain and mixed throat pain. Studies showed that activation of inflammatory and immune cells after RT induces release of inflammatory cytokines and chemokines promoting more cell damage inducing inflammatory pain in addition to activation of nociceptors causing nociceptive pain 32, 33, 102–104 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in this review, used either candidate gene approach or genome wide association analysis approach (GWAS), and interestingly through GWAS studies collected, we declared variants in genes involved in different/new pathways other than the common potential mechanisms of RT-induced pain, associated with RT-induced acute pain and toxicities. Sckack et.al conducted GWAS in HNC patients and identified candidate (rs1131769) in DNAJC18 gene regulating a chaperon molecules protecting cellular proteins, significantly associated with oral mucositis (OM) after RT 57 . Yang et.al did GWAS of NPC patients and identified variant (rs117157809) in Tankyrase (TNKS) gene regulating telomere capping and maintenance of telomerase activity, is significantly associated with RT-induced OM 59 .…”
Section: Discussionmentioning
confidence: 99%